2010
DOI: 10.1016/j.euroneuro.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier penetration of the enantiomers of venlafaxine and its metabolites in mice lacking P-glycoprotein

Abstract: , Blood-brain barrier penetration of the enantiomers of venlafaxine and its metabolites in mice lacking P-glycoprotein, 2010, European Neuropsychopharmacology, (20), 9, 632-640 Blood-brain barrier penetration of the enantiomers of venlafaxine in mice lacking P-gp Karlsson et al. 2 AbstractAccording to in vitro studies the enantiomers of venlafaxine display different degrees of serotonin and noradrenaline reuptake inhibition. Therefore, clarification of the enantiomeric drug distribution between serum and brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…However, venlafaxine has been reported to induce the expression of P-gp (Doran et al, 2005;Ehret et al, 2007) an effect not seen in our previous acute and chronic venlafaxine studies in the wild-type mouse (Karlsson et al, 2011;Karlsson et al, 2010). In another recently published study, venlafaxine was found to induce the expression of P-gp but no effect on induction was seen for desvenlafaxine (i.e.…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 57%
See 3 more Smart Citations
“…However, venlafaxine has been reported to induce the expression of P-gp (Doran et al, 2005;Ehret et al, 2007) an effect not seen in our previous acute and chronic venlafaxine studies in the wild-type mouse (Karlsson et al, 2011;Karlsson et al, 2010). In another recently published study, venlafaxine was found to induce the expression of P-gp but no effect on induction was seen for desvenlafaxine (i.e.…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 57%
“…In the present study, the ratio of citalopram concentration in brain between abcb1ab (-/-) mice and wild-type mice was 3.1 (1 h, acute). We showed recently for the antidepressant venlafaxine that the ratio of concentration in brain between abcb1ab (-/-) mice and wild-type mice ranges between 2.0 and 3.7 for the mother compound (Karlsson et al, 2011;Karlsson et al, 2010). These ratios might not be considered very high compared with some substances with higher affinity for P-gp e.g.…”
Section: And R-citalopram and Its Metabolites In Abcb1ab (-/-) Knocmentioning
confidence: 98%
See 2 more Smart Citations
“…Several researches have focused on the effect of P-gp in the brain distribution of different CNS-active or CNS-reactive therapeutic agents with the key finding being the role of P-gp as an efflux transporter limiting the brain penetration of its substrates (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%